Pengaruh Pelaksanaan Bimbingan Karir Terhadap Perancanaan Karir Peserta Didik Kelas F Lanjutan SMA Negeri 2 Sutera - Herman, Pebriani Yusnia; F, Firman; N, Netrawati (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Career planning is a crucial aspect of student development, especially at the senior high school level, as preparation for entering higher education and the workforce. However, in reality, many students still experience confusion and unpreparedness in making career decisions. Guidance and counseling services play a significant role in fostering career maturity among high school students. This study aims to determine the effect of career guidance implementation on the career planning of advanced class F students at SMA Negeri 2 Sutera. This research employs a quantitative approach using simple linear regression analysis. The population in this study consists of all 114 advanced class F students, with 83 respondents selected as samples using a simple random sampling technique. Data were collected through questionnaires and analyzed to examine the relationship between the implementation of career guidance and the clarity of students’ career planning. The results of this study are expected to contribute to improving the effectiveness of career guidance programs in schools to help students develop well-structured and potential-based career plans.